الترجمات الألبانية للقرآن الكريم في الفترة 1980م-2014م: دراسة تحليلية مقارنة - هاشاني، برات شاشوار (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The focus of this research revolves around all translations of the meanings of the Holy Qur'an either translated completely or partially into Albanian language during the last two centuries 20th and 21st. This research begins with the first attempt of the translation of the meanings of the Holy Qur'an into Albanian language. This research continues with some other attempts later in 20th century by some Albanian scholars to translate the meanings of the Qur'an of certain short surahs. This research follows the historical approach, the analytical approach and the comparative approach to study the aspects of the subject and reach the results, trying to answer the following research questions: What efforts were made by the Albanian scholars to serve the Quran and its translation and interpretation, and the value of these intellectual efforts and how to understand the Albanian people of the Holy Qur'an before these translations appear. Finally, the thesis concludes by focusing on two important translations between the translations of the meanings of the Qur'an to the Albanians: Translation of Dr. 'Feti Mehdiu' and the translation of 'Haxhi Sharif Ahmedi'. The research concludes that the translation of 'Dr. Feti Mehdiu' is the first full translation in the history of Albanians. The research concludes that the translation of 'Hafez Sherif Ahmeti' is the translation that is characterized by its methodology and the correct translation of its meanings from the first translation, as that is the translation typically read by most of the Albanian people.